On the structure of groups, whose subgroups are either normal or core-free - Kurdachenko, L.A.; Pypka, A.A.; Subbotin, I.Ya. (Доповіді НАН України, 2019)
We investigate the influence of some natural types of subgroups on the structure of groups. A subgroup H of the group
G is called core-free if CoreG(H) = 〈1〉. We study the groups, in which every subgroup is either normal or core-free.
More precisely, we obtain the structures of monolithic and non-monolithic groups with this property. Досліджується вплив деяких природних типів підгруп на структуру груп. Підгрупу H групи G називаємо
вільною від ядра, якщо CoreG(H) = 〈1〉 . Вивчено групи, в яких кожна підгрупа або нормальна, або вільна
від ядра. Точніше, одержано будову монолітичних та немонолітичних груп з цією властивістю. Исследуется влияние некоторых естественных типов подгрупп на структуру групп. Подгруппу H группы
G называем свободной от ядра, если CoreG(H) = 〈1〉 . Изучены группы, в которых каждая подгруппа либо
нормальна, либо свободна от ядра. Точнее, получена структура монолитических и немонолитических
групп с этим свойством.